The road to Xanadu : a study in the ways of the imagination - Lowes, John Livingston, 1867-1945 (Princeton legacy library., 1986)
John Livingston Lowes's classic work shows how various images from Coleridge's extensive reading, particularly in travel literature, coalesced to form the imagistic texture of his two most famous poems, The Rime of the Ancient Mariner" and "Kubla Khan."Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905